Malaysia and Singapore in Pictures - Nach, James (New York Sterling Publishing Co. Inc., 1972)
Photographs and brief text introduce the land, history, government, people, and economy of Malaysia and Singapore.
Include Maps and Illustration
Keywords: Malaysia -- Singapore